2002
DOI: 10.1104/pp.010108
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungal β-1,6-Glucanase Expression in the Infected Host Grass

Abstract: Mutualistic fungal endophytes infect many grass species and often confer benefits to the hosts such as reduced herbivory by insects and animals. The physiological interactions between the endophytes and their hosts have not been well characterized. Fungal-secreted proteins are likely to be important components of the interaction. In the interaction between Poa ampla and the endophyte Neotyphodium sp., a fungal ␤-1,6-glucanase is secreted into the apoplast, and activity of the enzyme is detectable in endophyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 55 publications
1
60
1
4
Order By: Relevance
“…The expression of lepus30a was also observed in mycelium and young fruiting body. This result implicates that the -1,6-glucanase also contributes in hyphal growth and branching, or development (Djonović et al 2006;Moy et al 2002).…”
Section: Endo-β-16-glucanasementioning
confidence: 83%
See 1 more Smart Citation
“…The expression of lepus30a was also observed in mycelium and young fruiting body. This result implicates that the -1,6-glucanase also contributes in hyphal growth and branching, or development (Djonović et al 2006;Moy et al 2002).…”
Section: Endo-β-16-glucanasementioning
confidence: 83%
“…Lichen Umbilicaria species produce a linear glucan composed of only β-1,6-linkages (pustulan; Nishikawa et al, 1970). Many fungi are considered to secrete β-1,6-glucanases, some of which have been purified and characterized (Bryant et al, 2007;Oyama et al, 2002;Moy et al, 2002;Pitson et al, 1996). All of the isolated enzymes are β-1,6-glucan endohydrolases (EC 3.2.1.75) classified into GH family 5 or 30 of the GH-A clan in the CAZy database.…”
Section: 1-glucanasesmentioning
confidence: 99%
“…In another symbiotic plant-fungus system, a ␤-1,6-glucanase was identified as being secreted into the apoplast of the host grass by its endophytic fungus, Neotyphodium sp. (40). Multiple functions for the enzyme were proposed, including the degradation of the cell walls of other fungi that may be encountered within the host plant.…”
mentioning
confidence: 99%
“…It was demonstrated that most endophytes are able to utilize, at least in vitro, most plant cell components. Most of investigated endophytes utilize xylan and pectin, show lipolytic activity and produce non-specific peroxidases and laccases (Sieber et al 1991;Leuchtmann et al 1992), chitinase ) and glucanase (Moy et al 2002). Endophyte may be a novel and good producer of xylanase (Suto et al 2002).…”
Section: Significance Of Endophytic Microorganismsmentioning
confidence: 99%